Globalland30 Mapping Capacity of Land Surface Water in Thessaly, Greece (2025)
Manakos I, K. Chatzopoulos-Vouzoglanis, Z.I. Petrou, L. Filchev, and A. Apostolakis. 2015. Globalland30 Mapping Capacity of Land Surface Water in Thessaly, Greece. Land 4(1): 1-18. https://doi.org/10.3390/land4010001.